Health care quality given in a comprehensive rehabilitation service with community base - Haydée Revilla Arias; Denny González Mustelier; Leydys Magda Valenzuela Fonseca (Centro Provincial de Información de Ciencias Médicas, 2016)
An investigation in health systems and services to evaluate the health care quality given in the Comprehensive Rehabilitation Service with community base, belonging to "Armando García Aspurú" Teaching Polyclinic in Santiago de Cuba, was carried out during  2013. The sample had 15 professionals and 180 patients, in whom surveys that were validated through alpha Cronbach coefficient were applied.  The process dimension was analyzed taking into account 15 approaches, indicators and standards.  When concluding the evaluation, 12 of these approaches were considered appropriate (80.0%); therefore, established standard was fulfilled. It was concluded that the health care aboved mentioned was optimal.